Entrepreneurial ecosystems as a bridging concept? A conceptual contribution to the debate on entrepreneurship and regional development - Bastian Lange; Suntje Schmidt (Growth and Change, 2021)
This paper explores the potential of considering entrepreneurial ecosystems as a bridging concept that enables a trans-disciplinary exchange. We aim to contribute to the debate by offering a perspective that takes entrepreneurial ecosystems out of their systemic—often geographically fixed—notion of administrative and territorial boundaries by offering a novel conceptual understanding of it. So far, entrepreneurial ecosystems are appreciated for first exhibiting conceptual strengths in terms of integrating entrepreneurs as economic actors (rather than firms as the smallest unit of analysis), and, second, considering entrepreneurship as a process that focuses on the co-evolution of entrepreneurial activities and their institutional environment. Criticism of this concept arises on its simplification by translating social elements into entrepreneurial ecosystem terminologies and on focusing on quantifiable indicators for measuring and comparing regional ecosystems rather than appreciating the complexity and interrelatedness of qualitative dimensions and their temporal dynamics. Against this background, we first argue for expanding the debate on entrepreneurial ecosystems by paying particular attention to the spatial as well as to temporal dynamics of entrepreneurship and its environment. Second, we regard entrepreneurial ecosystems as a communicative bridge that enables a fruitful exchange between academic disciplines and practitioners rather than approaching the concept as a mono-disciplinary theoretical framework.
Keywords: 300